If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) = x + 5x Reorder the terms: 2(-5 + x) = x + 5x (-5 * 2 + x * 2) = x + 5x (-10 + 2x) = x + 5x Combine like terms: x + 5x = 6x -10 + 2x = 6x Solving -10 + 2x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -10 + 2x + -6x = 6x + -6x Combine like terms: 2x + -6x = -4x -10 + -4x = 6x + -6x Combine like terms: 6x + -6x = 0 -10 + -4x = 0 Add '10' to each side of the equation. -10 + 10 + -4x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -4x = 0 + 10 -4x = 0 + 10 Combine like terms: 0 + 10 = 10 -4x = 10 Divide each side by '-4'. x = -2.5 Simplifying x = -2.5
| (x^2-4x+4)/(x^2+4x-12)*(2x+12)/(6x^2-13x+2) | | s^2+6s+5=0 | | (2/x)+4=(2/3x) | | 8m-29=-22+7m | | 13.7b-6.5=23b+8.3 | | 5n-25=-13+3n | | -7.64+10000= | | y=-3*1+2 | | y=-3*-2 | | 0.6(y+1.5)=-2.1(y-3) | | 6(3+3x)-2=106 | | -2/5(n-1/8)=1/2(n-1/6) | | 10-2m=3m+25 | | 1729x-258=433x-474 | | (2/x^2+12x+36)+(5/x^2+x-30) | | X^2+10x+9=(x+1)(ax+b) | | -2(x-3)+4(2-x)= | | -5y-8=-7y-16 | | 19x-11-17x+14=2x+3 | | [5x-7]=33 | | 8-[(-3+7)-(3-9)]= | | 5+4x-7=4x-2 | | -10-(-3)= | | 0-8y=5 | | -4.07+2.3= | | T=C(2+AB) | | 5(2y+2)-(y+3)= | | abs(3x-4)= | | 1/3t-4/3=5/4t-3/2 | | 3(2x-1)-2(x-4)= | | 8m-5=6m-8 | | (5x-4)(4x+9)=0 |